A comprehensive review of marine sponge metabolites, with emphasis on Neopetrosia sp. - Noora Barzkar; Stanislav Sukhikh; Olga Babich (Elsevier, 2024)
The secondary metabolites that marine sponges create are essential to the advancement of contemporary medicine and are often employed in clinical settings. Over the past five years, microbes associated with sponges have yielded the identification of 140 novel chemicals. Statistics show that most are derived from actinomycetes (bacteria) and ascomycotes (fungi). The aim of this study was to investigate the biological activity of metabolites from marine sponges. Chlocarbazomycins A-D, which are a group of novel chlorinated carbazole alkaloids isolated from the sponge Neopetrosia fennelliae KUFA 0811, exhibit antimicrobial, cytotoxic, and enzyme inhibitory activities. Recently, marine sponges of the genus Neopetrosia have attracted attention due to the unique chemical composition of the compounds they produce, including alkaloids of potential importance in drug discovery. Fridamycin H and fridamycin I are two novel type II polyketides synthesized by sponge-associated bacteria exhibit antitrypanosomal activity. Fintiamin, composed of amino acids and terpenoid moieties, shows affinity for the cannabinoid receptor CB 1. It was found that out of 27 species of Neopetrosia sponges, the chemical composition of only 9 species has been studied. These species mainly produce bioactive substances such as alkaloids, quinones, sterols, and terpenoids. The presence of motuporamines is a marker of the species Neopetrosia exigua. Terpenoids are specific markers of Neopetrosia vanilla species. Although recently discovered, secondary metabolites from marine sponges have been shown to have diverse biological activities, antimicrobial, antiviral, antibacterial, antimicrobial, antioxidant, antimalarial, and anticancer properties, providing many lead compounds for drug development. The data presented in this review on known and future natural products derived from sponges will further clarify the role and importance of microbes in marine sponges and trace the prospects of their applications, especially in medicine, cosmeceuticals, environmental protection, and manufacturing industries.